N-Halo Reagents: Modern Synthetic Approaches for Heterocyclic Synthesis - de Andrade, Vitor S.C.; de Mattos, Marcio C.S. (Synthesis, 2019)
Heterocyclic chemistry is an essential frontier in science and a source of novel biologically active compounds. The development of innovative synthetic methodologies that allows access to different heterocyclic rings is of critical interest to the scientific community. This review will focus on recent applications of N-halo compounds (e.g., N-halosuccinimides, trihaloisocyanuric acids, N-halosulfonamides, etc.) in heterocyclic construction via electrophilic cyclization, asymmetric halocyclization, oxidative cyclization, and radical processes.1 Introduction2 N-Halo Reagent Mediated Heterocyclic Construction and Functionalization2.1 Electrophilic Halocyclizations2.1.1 Asymmetric Halocyclizations2.2 Radical Halocyclizations2.3 Oxidative Halocyclizations2.4 Miscellaneous Halocyclization Reactions3 Summary and Outlook
Keywords: heterocycles; N-halo compounds; electrophilic cyclization; N-haloimides; asymmetric halocyclization; condensation; oxidative cyclization